ANALISIS UNSUR KETAATAN DALAM FILM THE BOOK OF DANIEL PRODUKSI PURE FLIX ENTERTAIMENT - Tompodung, Omega O. M.; Wantasen, Isnawati L.; Lasut, Theresia M.C (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2021)
Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â AbstractThe research is entitled â€œObedience in the Film The Book of Daniel Produced by Pure Flix Entertaimentâ€. It is written to fulfill the requirement of accomplishing bachelorâ€™s degree in English department Faculty of Humanities Sam Ratulangi University. The focus of this research is obedience in the film the Book of Daniel, which is reflected in the character of Daniel. The aims of this research are to identify, classify and analyze the theme in the Film the Book of Daniel through the characters. The writer uses the theory of Grace (2009) to analyze the major theme in the Film The Book of Daniel through the character and plot, and Martin (1995) as theory of religious film as a hagiopic genre, which tells the life of someone as a hero of religion. The writer also uses the theory of Klarer (1998) to analyze of the film. In addition, the writer also uses the theory of Weiss (1998, to analyze the obedience expressied in the film. The result of this research shows the 7 types of obedience action. The 7 types of obedience are, obedience eats certain foods, obedience to prayer, obedience listening, ethical obedience, obedience in patience, obedience in loyalty only to God, obedience in accepting punishment. The 7 types of obedience action are certain foods, pray, do not worship the golden statue, speak the truth, not worhip humans, waiting in patientlyKeywords: Obedience, Character, Film, Moral Value, History